Selection of Reference Genes for Microrna Analysis Associated to Early Stress Response to Handling and Confinement in Salmo Salar - Vidal-Soto, R (Nature Publishing Group, 2017)
MicroRNAs are key non-coding RNA molecules that play a relevant role in the regulation of gene expression through translational repression and/or transcript cleavage during normal development and physiological adaptation processes like stress. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) has become the approach normally used to determine the levels of microRNAs. However, this approach needs the use of endogenous reference. An improper selection of endogenous references can result in confusing interpretation of data. The aim of this study was to identify and validate appropriate endogenous reference miRNA genes for normalizing RT-qPCR survey of miRNAs expression in four different tissues of Atlantic salmon, under handling and confinement stress conditions associated to early or primary stress response. Nine candidate reference normalizers, including microRNAs and nuclear genes, normally used in vertebrate microRNA expression studies were selected from literature, validated by RT-qPCR and analyzed by the algorithms geNorm and NormFinder. The results revealed that the ssa-miR-99-5p gene was the most stable overall and that ssa-miR-99-5p and ssa-miR-23a-5p genes were the best combination. Moreover, the suitability of ssa-miR-99-5p and ssa-miR-23a-5p as endogeneuos reference genes was demostrated by the expression analysis of ssa-miR-193-5p gene. © 2017 The Author(s).